SCAPS simulated FASnI3 and MASnI3 based PSC solar cells: A comparison of device performance. Issue 1 (1st January 2022) - Vishnuwaran, M.; Ramachandran, K.; Roy, Priyanka; khare, Ayush
Abstract: In this paper, we have designed simulated, compare, and analyzed the high efficiency of FASnI3 and MASnI3 based PSC solar cell. In recent times, organic and inorganic Perovskite-based solar cells are turning to be hopeful devices due to their unique proprieties in the PV field. In our present work, we were concentrating several studies on Perovskite solar cell-based FASnI3 and MASnI3 Perovskite layer. Most of the Perovskite solar cell is made by Pb material for getting the high efficiency. However, the factor of toxicity and stability of the Pb-constructed devices is the main challenge to progress in commercial manufacture. In this study, numerical modeling of PSC used the alternative materials which are Sn-based Perovskite solar cells. In this work, we investigated tin-based perovskite solar cells with different absorber layers and also we investigated using high thickness in ETL and HTL what are change could be happen these are the things also we discussed in this paper. If we increase the thickness of the ETL and HTL the efficiency also increased we got some good results on it. Here we report simulation of lead-free Tin based PSC processed on FASnI3 and MASnI3 two different Perovskite layers. In our present work, we using 1D-SCAPS for numerical analysis.